Design of a wide range kVp-meter - Tümer, Murat. (Thesis (M.S.)-Bogazici University. Institute of Biomedical Engineering, 2007., 2007)
The kVp setting is one of the major factors affecting the image quality in X-ray imaging and should be annually measured and calibrated if necessary. In this thesis, a kVp-meter is designed and a prototype unit was built and the performance was tested in terms of accuracy and reliability. The design is based on the dependency of the attenuation coefficient of metals on the energy of the incident photons, which is related to kVp. The tests on the prototype showed that the accuracy and precision are both below 1% in the diagnostic range. As the same measuring principle applies for mammography unit, this device can be also used for kVp measurements of mammography units. The accuracy and precision in the mammography mode are below 1%, too.|Keywords: Kilovolts peak, X-ray, photodiode, copper filter, linear attenuation coefficient, calibration.
Keywords: X-rays.; Photodiodes.; Calibration.